Male vigilance and presence are important for foraging by female Chinese grouse in the pre‐incubation period. (5th June 2017) - Lou, Yingqiang; Shi, Mei; Fang, Yun; Swenson, Jon E.; Lyu, Nan; Sun, Yuehua
Abstract : In some monogamous birds, males invest more time in vigilance than females, especially during the pre‐incubation period. As behaviors are time costly, there is a tradeoff between vigilance and feeding behavior. Male vigilance can be regarded as a male investment in their mates and may benefit the female by reducing the danger of predation, increasing her probability of survival, and allowing more time for her to forage to obtain more resources for egg production and incubation. In this study, we documented the proportion of time spent in vigilance and feeding by Chinese grouse Tetrastes sewerzowi with their mates and alone during the pre‐incubation period, and then estimated male vigilance under more severe predation pressures through predator call playback. Our results indicated that paired male Chinese grouse spend more time in vigilance than unpaired males and paired females and could alter their activity budgets in response to the social context (i.e. with and without their mate) and an experimental encounter with an important predator. Male vigilance behavior and presence allowed females to spend more time foraging. We therefore conclude that vigilance behavior by their male partners by may play an important role in promoting the females' survival and probably the reproductive success. The proportion of time allocated for vigilance by males and foraging by females of Chinese grouse during the pre‐incubation period was the highest recorded among monogamous grouse species, perhaps because the Chinese grouse is the smallest grouse species and has the highest relative reproductive investment.